PERENCANAAN STRATEGI SISTEM INFORMASI PADA SEKOLAH DASAR ISLAM TERPADU MIFTAHUL ULUM GANDUL MENGGUNAKAN METODE CASSIDY - Leliyanah Leliyanah (Paradigma, 2013)
Nowdays, Information system (IS) and Information Technology (IT) was giving benefit inindustrial used. Development of SI/TI must be align with organization direction. Creating ITstrategic planning is a step for company that want better business environtment in the future.Analyze from many current factors, internal and external so can realize management strategy thatalign with IT strategy. Approach methode used was Anita Cassidy. Cassidy is a strategic planningprocess can be carried out based on the main components of the business are like vision, mission,goals and or budget. Although the planning process will take time and effort to sharpen thebusiness plan before stepping on the planning of IS/IT Cassidy methode have four phase :visioning, analysism direction and recommendation. Hopely with this approach can resultrecommended IT strategy that suit with company business direction.Keywords: Cassidy methode, IT/IS Strategic Planning, Mc Farlan Gri, SWOT Analysys